HYDROLOGICAL STUDY ON LIMESTONE MINE DRAINAGE SYSTEM IN PT. ADS - SOUTH SUMATERA - Charly Bravo Wanggai; Ceni Febi Kurnia Sari (USN Kolaka, 2020)
The groundwater availability in an area with mineral deposits is measured by the geological and geomorphological characteristics of the area. The hydrological study on limestone mining in PT. ADS, South Sumatera aimed to acquire data and information regarding rainfall characteristics, drainage basin and catchment area, infiltration value, and surface water flow pattern at the limestone mining site and nearby area; this is to formulate a basis of reference in creating drainage system. The study employed Extreme Value Gumbel formula to analyze the expected daily rainfall. A calculation on the rainfall return period relied on two factors, i.e., the planned mining duration and natural events, such as seasonal flood per two years. Moreover, Mononobe formula was used to calculate and convert the daily rainfall intensity in the form of hourly rate. The mine drainage system was regarded necessary in the site since the watery area is potential to hinder the production as well as to cause work accidents; on top of that, the terrain is dominated by relief of wavy hills with varying waves and slopes ranging from 10°-70°.